Anteseden dari Purchase Intention pada Konsumen Columbia Cash dan credit Metropolitan Mall Bekasi - Said, Muh. (Jurnal Office, 2018)
The background of this research is many factor can influence the customer purchase intention, some determinant have been study. This study is to understand the way of brand and store name, and the price to influence customer purchase intention at Colombia cash and credit electronics shoppers in Bekasi, West Java. The objective (s) of this research was to understand if they are having an effect between price discout toward internal reference price and perceived brand quality; an effect between brand name dan store name toward perceived brand quality and perceived store image; and then effect between internal reference price, perceived brand quality and perceived store image toward perceived value can mount purchase intention at consumers comments Columbia Cash and Credit in area Metropolitan Mall Bekasi. Data analyze used in this research is primer data and using simple random sampling to collect the data, analysis data method in this research is using Multiple Regression Method. Respondent in this research are the consumers Columbia Cash and credit in Metropolitan Mall Bekasi. The result of this research found that this study have a evidance that price discount, brand name and store name is very effective in influence and stimulating effort to the customer purchase intention, so the suggested from the study it’s possible to run the price discount, but it’s must been run at the right moment, so it will be give fascination to draw consumer enthusiasm and the finally conduct the tansaction.